Existence of Positive Solutions to Multi-Point Third Order Problems With Sign Changing Nonlinearities - Dogan, Abdulkadir; Graef, John R. (Univ Tartu Press, 2020)
In this paper, the authors examine the existence of positive solutions to a third-order boundary value problem having a sign changing nonlinearity. The proof makes use of fixed point index theory. An example is included to illustrate the applicability of the results.
Graef, John/0000-0002-8149-4633;
Keywords: Differential Equation; Third-Order; Boundary Value Problem; Positive Solutions; Fixed Point Index